A self-healing supramolecular hydrogel with temperature-responsive fluorescence based on an AIE luminogen. Issue 12 (17th February 2020) - Li, Botian; Zhang, Yichi; Yan, Bo; Xiao, Da; Zhou, Xue; Dong, Junwei; Zhou, Qiong
Abstract : A supramolecular hydrogel was synthesized by using tetra(4-(pyridin-4-yl)phenyl)ethylene (TPPE) as AIE luminogen. The gel not only featured self-healing performance, but also exhibited the temperature-responsive fluorescence with thermochromism. Abstract : In this work, an AIE luminogen-based hydrogel with temperature-responsive fluorescence was designed and synthesized. The polymeric hydrogel consisted of a supramolecular network through coordination and ionic interactions. When the temperature was decreased, due to the motion restriction of the polyacrylic acid macromolecular segments and the enhancement in ionic interaction, the hydrogel exhibited a blue-shift in the fluorescence emission peak and increase in the fluorescence intensity, resulting in the visualization of fluorescence changes. The hydrogel network benefitted from non-covalent crosslinking and thus possessed self-healing properties at room temperature with good toughness and resiliency. Therefore, this fluorescent supramolecular hydrogel might be used as a temperature-responsive material.